Realization of DVCCTA Based Versatile Modulator - Neeta Pandey; Rajeshwari Pandey; Aseem Sayal; Manan Tripathi (Active and Passive Electronic Components)
A Differential Voltage Current Conveyor Transconductance Amplifier (DVCCTA) based versatile modulator is proposed which can work as an amplitude modulator, frequency modulator, delta modulator, and sigma delta modulator. The modulator operational scheme uses pulse generator as a core and its output is used as carrier signal. A DVCCTA based pulse generator is proposed first and subsequently configured as different modulators. Compact realization is the key feature of the proposed circuit as it uses two DVCCTA; a grounded resistor and a grounded capacitor hence are appropriate for IC realization. The functionality of the proposed circuit is verified through SPICE simulations using TSMC 0.25 μm CMOS process model parameters. The performance parameters such as power dissipation and noise for various modulator schemes are also obtained.